THE PHENOMENON OF HAPPINESS AND WELL-BEING IN THE CREATIVE HERITAGE OF AHATANHEL KRYMSKYI: A PHENOMENOLOGICAL AND EXISTENTIAL DIMENSION - Yarmolitska, Nataliia; Liashenko, Iryna (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2026)
Background. The article presents a phenomenological and existential analysis of the experience of happiness and well-being in the creative heritage of Ahatanhel Krymskyi. The relevance of the study is determined by the need for a philosophical and cultural reflection on the transformations of conceptions of happiness in contemporary Ukrainian culture, particularly under the conditions of war, collective trauma, and the reassessment of existential values. The main attributive characteristics of happiness are identified as an internal, intense, and existentially contradictory experience. The differences and points of intersection between the model of happiness represented in Krymskyi’s works and the dominant notions of happiness and well-being in contemporary Ukrainian culture are outlined. It is demonstrated that the existential solitude, intellectual reflexivity, and axiological tension characteristic of Krymskyi fundamentally contradict contemporary narratives focused on psychological comfort, social stability, and emotional harmony. Methods. The methodological framework of the study is based on the phenomenological approach, existential-philosophical analysis, and hermeneutic interpretation of literary texts. Cultural studies and comparative methods are also employed to juxtapose the attributive characteristics of happiness and well-being in Krymskyi’s creative legacy with those prevalent in the contemporary Ukrainian cultural context. Results. It is established that in the novel "Andrii Lahovskyi", happiness appears as an internally tense, reflective, and anti-hedonistic experience, inseparable from solitude, suffering, and spiritual quest. The key attributive features of this experience are identified as interiorization, tragic sensibility, existential solitude, and the prioritization of meaning over comfort. Comparative analysis demonstrates that contemporary Ukrainian culture, despite the dominance of psychologized models of well-being, increasingly actualizes—under wartime conditions—an existential understanding of happiness as the capacity to preserve dignity, meaning, and solidarity in extreme situations. Conclusions. The study confirms that the phenomenon of happiness in the works of Ahatanhel Krymskyi possesses a pronounced existential and phenomenological character and remains relevant for interpreting contemporary Ukrainian experience. Krymskyi’s creative heritage emerges as a cultural and philosophical resource that enables a rethinking of well-being beyond utilitarian comfort and psychological stability, emphasizing the significance of meaning, inner resilience, and authenticity.